Meningkatkan Kemampuan Manajemen Konflik Melalui Konseling Kelompok - Prahesti Khasanah (Universitas Ahmad Dahlan, 2014)
This study aims to determine efetivitas group counseling in improving conflict management students. This type of research used in this research is action research in guidance and counseling (PTBK). The research was conducted at SMK N 5 Yogyakarta, at Jl. Walnuts 71 Rt 21 Rw 07 Muja Muju Umbulharjo Yogyakarta. When the study was conducted in the first semester of the academic year 2014/2015, with research subjects timber A class XI student of SMK N 5 Yogyakarta TA. 2014/2015, amounting to 8 students. Tenik sampling using purposive sampling and data analysis techniques used to examine differences between the mean pretest and posttest after the action using t-test formula. The results of this research that there is an increase conflict management capacity at the student based on the pretest and posttest that shows that before the given action in the form of group counseling services in the medium category with the number 6 frequency by 75% and the high category with a number of second frequency by 25%. Once given the actions that are in the high category with a number of frequency of 4 by 50% and very high category with a frequency of 4 by 50%. Information from this research for teachers BK can be used as a basis for development of group counseling services to help increase conflict management capacity within each student. The results of this study may also be useful for parents, principals, deputy principal of student field, homeroom and subject teachers as information in an effort to improve students' ability of conflict management.